The results of applied research for solutions to environmental problems, expected! - Dolly Priatna; Kathryn A. Monk (Universitas Pakuan, 2021)
With this issue, the Indonesia Journal of Applied Environmental Studies (InJAST) enters its second year, having been first published in April 2020 just as the Covid-19 pandemic was spreading globally. In the first two issues, InJAST published 13 articles, which were the results of research and ideas from academia, researchers from the Indonesian Institute of Sciences (LIPI) and members of conservation NGOs. Within its first year, the InJAST website has been visited by around 1,500 visitors from 50+ countries. Although the majority were from Indonesia, 30% were from across Europe, Asia, the Americas, and Africa, and included the USA, UK, Australia, and India.One of InJAST's missions is to provide a vehicle for academia (students and lecturers), members of environmental NGOs, and young researchers, particularly from Indonesia, who are just starting to publish their ideas, literature reviews and research findings or articles in scientific journals. InJAST was also developed to accommodate scientific papers related to broader environmental topics, but as yet, most articles have focused on plant/wildlife ecology, nature conservation, and forest restoration (61%). Others were the result of the studies on environmental education (8%) and on the UN Sustainable Development Goals (SDGs) and other environmental issues (31%).As we start the third decade of the 21st century, the environmental challenges we face are ever more complex and demanding. The UN’s global action plan for the next 10 years set out in the